The Effect of Principal Transformational Leaders and Work Motivation on Teacher’s Performance - Nurul Rizqi Azizah; Wahidin Wahidin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The aim of this study was to find out whether the transformational leadership of principals and work motivation had a positive and significant influence on the performance of North Jakarta State Vocational High School teachers. The method in this study uses quantitative approaches by conducting surveys and multiple linear regression techniques with preceded normality tests and linearity tests. The population in this study was 307 teachers using the Slovin sample technique with a 10% error rate of 75 teachers. This research instrument uses a Google form questionnaire based on the likert scale. Hypothesis testing is performed by conducting tests of normality, significantness, linearity, multicollinearity, heteroskedasticity, T, F, and determination tests. The results of this study showed that transformational leadership and teacher performance had a positive and significant effect with a grade of T = 4,675 with sig,000 0.05, This means that transformational leadership styles are effectively used by principals to improve teacher performance. Work motivation has a positive and significant effect on teacher performance with a value of T = 11.37 with sig.0000.05, meaning that the work motivation of teachers and principals is very influential for improving teacher performance positively. And overall based on the determination test of 64.2% means that transformational leadership and work motivation simultaneously have an influence on improving the performance of teachers of North Jakarta State Vocational School by 64.2%.